Generation mechanism of negative permittivity and Kramers–Kronig relations in BaTiO3/Y3Fe5O12 multiferroic composites. (7th August 2017) - Wang, Zhongyang; Sun, Kai; Xie, Peitao; Liu, Yao; Fan, Runhua
Abstract: Recently, negative parameters such as negative permittivity and negative permeability have been attracting extensive attention for their unique electromagnetic properties. Usually, negative permittivity is well achieved by plasma oscillation of free electrons in conductor–insulator composites or metamaterials, while some attention has been paid to attaining negative permittivity in ceramics to reduce dielectric loss. In this paper, negative permittivity in barium titanate and yttrium iron garnet composites are reported which was well fitted by the Lorentz model. Further, negative permittivity behavior was verified via Kramers–Kronig relations, and it revealed that the causal principle still valid for negative permittivity resulted from dielectric resonance. The interrelationships among negative permittivity, capacitive–inductive transition and ac conductivity are discussed.